Improvement of Communicative-pragmatic Ability in Adolescents with Autism Spectrum Disorder: The Adapted Version of the Cognitive Pragmatic Treatment. Issue 1 (2nd January 2022) - Gabbatore, Ilaria; Longobardi, Claudio; Bosco, Francesca M.
ABSTRACT: Autism spectrum disorder (ASD) is a complex pathology that includes impaired social interaction abilities. Insufficient attention has been paid to programs specifically devoted to improving communicative-pragmatic skills. Moreover, the majority of studies have focused on children, while programs specifically developed for the adolescents are lacking. The present study aims to test the feasibility and acceptability of the adapted version of the Cognitive Pragmatic Treatment for adolescents (A-CPT), a 15-session group training, as well as its ability to improve the communicative-pragmatic performance of adolescents with ASD. Twenty-one verbally fluent adolescents with ASD took part in the training; they were assessed in three phases, i.e., before, after and at three-month follow-up, using the equivalent forms of the Assessment Battery for Communication (ABaCo), a tool for testing a wide range of pragmatic phenomena, such as direct and indirect speech acts, irony, deceit and violation of Grice's maxims, expressed through linguistic, non-verbal, i.e., gestures, or paralinguistic expressive means. Furthermore, Theory of Mind (ToM) tasks and tests investigating the main cognitive domains, for example, Executive Functions (planning, shifting, working memory) and long-term memory, were administered. The results showed an improvement in participants' performance in all the four scales of the ABaCo, i.e., linguistic, extralinguistic, paralinguistic and context scale; this improvement was maintained at follow-up assessment three months after the end of the program. No improvement was observed in the cognitive and ToM domains investigated, with the only exception of expressive vocabulary task. Despite the lack of a control group, the high degree of feasibility of the CPT, highlight the importance of more work needed in this research line.